Therapeutic role of flavonoids and flavones in cancer prevention: Current trends and future perspectives - Azhar U. Khan; Hanuman S. Dagur; Masudulla Khan; Nazia Malik; Mahboob Alam; Md Mushtaque (Elsevier, 2021)
Cancer is one of notorious diseases across the globe.Therapeutic approaches for cancer are often expensive and develop severe side effects, and usually result comorbidities among the cancer survivors. Identifying novel therapies for treatment will reduce comorbidities in curing these diseases. It has been reported that flavones, a sub-class of flavonoid can act as a potent anticancer agent. Many experimental results displayed that flavones modulate signal transduction pathways in carcinogenesis. Flavones have been found to control cell cycle progression, oxidative stress, angiogenesis and metastasis alongwith some molecular pathways that ultimately prevent the progression of the diseases. Flavones have shown to possess a considerable as cancer preventive agents. As per the reports, flavones rich diet is beneficial, decreased risk of breast cancer, skin, digestive system, certain hematological malignancies and prostate cancer. Apart from cancer, flavones are also effective in improving other disease conditions such as cardiovascular and neurological diseases. Hence, these are the prime target in natural product and drug discovery research. Based on existing findings, it can concluded that more extensive research is needed to understand detailed beneficial properties of flavones along with biochemical mechanisms that drive these medicinal properties.